Body condition score, morphometric measurements and estimation of body weight in mature Icelandic horses in Denmark. Issue 1 (October 2016) - Jensen, Rasmus; Danielsen, Signe; Tauson, Anne-Helene
Abstract Background Obesity is related to the development of several diseases like insulin resistance and laminitis in horses. The prevalence of obesity among mature Icelandic horses in Denmark has not been investigated previously. This study aimed to find the prevalence of obesity, to compare body condition score (BCS) based on owner perception with that of an experienced person and to correlate the BCS to body weight (BW) and morphometric measures in a group of mature Icelandic horses in Denmark. A total of 254 Icelandic horses (≥4 years; 140 geldings, 105 mares, 9 stallions) from 46 different farms were included. All horses were assigned a BCS on a scale from 1 to 9 (1 is poor, 5 is moderate and 9 is extremely fat) by their owner and by an experienced person. Two weight tapes were used to assess BW. Girth circumference (GC), neck circumference (NC) and height at withers (HW) were measured, and the GC:HW and NC:HW ratios were calculated. Results Categorising the horses into four groups, 5.9 % were underweight (BCS 3–4), 70.1 % were optimal (BCS 5–6), 13.8 % were overweight (BCS 7) and 10.2 % were obese (BCS 8–9). The GC:HW and NC:HW ratios increased with increasing BCS, as did the BW estimated with the weight tapes. A GC:HW ratio >1.21 might indicate overweight or obesity in Icelandic horses. Horse owners underestimated the BCS of their horses compared to an experienced person. Conclusions The results from this study show that 24.0 % of mature Icelandic horses in Denmark are overweight or obese, and that owners tend to underestimate the BCS of their Icelandic horses. The GC:HW ratio might indicate overweight or obesity, however, the ratio for Icelandic horses is different than reported for horses and ponies of other breeds.